Helminthofauna of the pine marten (Martes martes) in Central Russia - O. A. Panova; A. V. Khrustalev; O. N. Andreyanov; A. S. Lapasova; K. S. Kuznetsov (Российский паразитологический журнал, 2025)
The purpose of the research is to study of the fauna of helminths of the pine marten (Martes martes) in the Ryazan region.Materials and methods. The material for the work was carcasses or individual organs of the pine marten, delivered from the territory of hunting grounds of the Ryazan region, obtained as a result of licensed hunting. Whole carcasses were examined by the method of complete helminthological dissection, in case of receipt of individual organs, an incomplete dissection was performed. The material from 91 animals was examined.Results and discussion. According to the results of helminthological examination of the pine martens 23 species of parasites were identified: 13 species of nematodes, 2 species of cestodes, 6 trematodes and 2 acanthocephalans. All examined animals were infected (100%). The following nematodes were found in the gastrointestinal tract: Aonchotheca putorii (86.6%), Molineus patens (13.4%), Strongyloides martis (4.9%); cestodes Taenia martis (15.4%), Mesocestoides lineatus (1.2%); acanthocephalans Centrorhynchus sp. (19.5%); trematodes Isthmiophora melis (29.3%), Apophallus donicus (9.8%). Three species of trematodes were found in the liver: Metorchis bilis (6.8%), Pseudamphystomum truncatum (5.1%) and Opisthorchis felineus (1.7%). The paranal glands contained nematodes Capillaria paranalis (55.3%). In the lungs and trachea, 5 species of nematodes were found: Eucoleus aerophilus (96.4%), Filaroides martis (50.6%), Sobolevingylus skrjabini (36.1%), Crenosoma petrovi (25.3%), Aelurostrongylus falciformis (2.4%). In the nasal cavity of 73.1% of martens, the nematode Skrjabingylus petrowi was found. In the urinary bladder of 40.9% of martens, there were nematodes Pearsonema mucronata. In the muscle tissue, Trichinella were found in 6.8% of martens. Alaria larvae were found in the connective tissue of 15.4% of martens. The most common are Eu. aerophilus (96.4%), Ao. putorii (86.6%) and Skr. petrowi (73.1%). High infection rates in the natural environment indicate the formation of stable foci of parasitosis in the region.